Myasthenia gravis and concurrent myositis following PD-L1 checkpoint inhibitor for non-small cell lung cancer. Issue 1 (19th March 2020) - Phua, Chun Seng; Murad, Ari; Fraser, Clare; Bray, Victoria; Cappelen-Smith, Cecilia
Abstract : Background: There are increasing reports of myasthenia gravis (MG) following oncological treatment with immune checkpoint inhibitors (ICIs). Methods and results: A 66-year-old man with stage 3A lung adenocarcinoma was treated with second weekly infusions of durvalumab, a programmed cell death ligand-1 inhibitor, at a dose of 10 mg/kg. After the fourth infusion, he developed diplopia, dyspnoea and constitutional symptoms including headache, weakness and anorexia. 1 month later, he developed dysphagia and dysphonia. Examination showed proximal limb weakness with fatigability. An ice pack test was positive. Blood tests revealed a raised creatine kinase and positive PM-Scl75 antibody. Antititin antibody was strongly positive in the serum and cerebrospinal fluid. Antibodies for acetylcholinesterase receptor and antimuscle-specific kinase were negative. Electromyography showed myopathic changes. The patient was treated with steroids, pyridostigmine, mycophenolate mofetil and intravenous immunoglobulin. Eight weeks after treatment initiation ptosis, eye movements and limb strength were markedly improved and repeat creatine kinase was normal. Conclusion: Clinicians using ICIs should have a high index of suspicion for ICI-induced MG and concurrent myositis as disease can be severe and is associated with high mortality rates.